Impact of transportation on climate change: An ecological modernization theoretical perspective. (January 2023) - Pal, Preeti; Gopal, P.R.C.; Ramkumar, M.
Abstract: Among the various climate change causing agents, transportation alone is responsible for 19.2% of the carbon emissions. By proper implementation of various preventive measures, the impact of transportation on climate change can be drastically reduced. It is also necessary to determine the relationship between the transportation factors responsible for creating environmental degradation and causing climate change and to rank them based on the preventive measures impact to deal with them. In this paper, we have identified the transportation factors that affect climate change and the factors related to its preventive measures based on the 'environment', 'sociology' and 'modernity' elements of Ecological Modernization Theory (EMT). Given the context, this study focusses on development of an assessment framework that combines three techniques: Simple Additive Weighting (SAW), Interpretive Structural Modelling (ISM) and Interpretive Ranking Process (IRP). Highlights: We integrate SAW-ISM-IRP approach to understand the impact of transportation on climate change. We have identified the factors based on Ecological Modernization Theory. First, SAW has been used to reduce the number of factors in order to apply ISM and IRP easily. We have collected data from 10 experts.